Long-term seroprotection after an adolescent booster meningococcal serogroup C vaccination. Issue 9 (13th July 2013) - de Whalley, Philip C S; Snape, Matthew D; Plested, Emma; Thompson, Ben; Nuthall, Elizabeth; Omar, Omar; Borrow, Ray; Pollard, Andrew J
Abstract : Objectives: To determine long-term seroprotection after serogroup C meningococcal (MenC) vaccination at the age of 9–12 years, with or without booster vaccination at the age of 13–15 years. Design: Observational cohort study; follow-on from randomised study. Setting: Participants were recruited from English secondary schools (in Oxfordshire and Buckinghamshire). Participants and interventions: Participants were primed with MenC CRM-glycoconjugate vaccine at the age of 9–12 years in the UK routine immunisation campaign. In previous studies they were randomised at 13 to 15 years of age to receive a booster dose of MenC-CRM glycoconjugate vaccine (CRM-group) or bivalent meningococcal serogroup A/C polysaccharide vaccine (PS-group), or they received no additional doses of MenC vaccine (control group). In this follow-on study, a blood sample was obtained 11 years after primary immunisation. Of 531 individuals eligible to participate, 134 were enrolled, and 124 were included in the analysis. Main outcome measures: MenC serum bactericidal antibody (SBA) geometric mean titre; proportion of participants with SBA titre ≥8 (putative protective threshold). Results: Median ages at priming, boosting and blood sampling were 10.61, 14.42 and 22.11 years, respectively. Geometric mean titres for MenC SBA were: CRM group 1373 (95% CI 954 to 1977); PS group 1024 (687 to 1526); and controls 284 (167 to 483). SBA titres ≥8 were present in 50/54 (92.6%) controls and 70/70 (100%) boosted individuals. Conclusions: The planned introduction in the UK of an adolescent booster of MenC conjugate vaccine in 2013 is likely to provide sustained protection against MenC disease. Trial registration: Registered on ClinicalTrials.gov (NCT01459432 ).